Physical oceanography at CTD station GeoB24339-1 during RV SONNE cruise SO278 in 2020 at the Mediterranean Ridge - Gerhard Bohrmann; Stefanie Gaide (PANGAEA, 2021)
The main objective of the RV SONNE cruise SO278, which took place between 12.10.2020 to 01.12.2020 was to investigate the interactions between the seabed and ocean water in Greek waters, whereby the plate tectonic constellation of a broad collision zone represents a special tectonic drive. In total, six CTDs were deployed, mainly to sample the methane content in the water column. Oceanographic data as well as water samples were collected at the Olimpi mud volcano field (flare position, Milano MV, Napoli MV), United Nations Rise (Dublin MV), in the fault zone at the northern part of the Mediterranean Ridge and at the site of a subrosional brine pit close to the Nadir brine lakes. Detailed information about the temperature, conductivity and oxygen of the water column have been carried out with a Seabird CTD/Rosette with additional SBE 43 oxygen sensor and a fluorometer. The Rosette contains 24 Niskin bottles with a volume of 10 l.